DETERMINATION OF EARTH SCIENCE PRINCIPLES DESIRABLE FOR INCLUSION IN THE SCIENCE PROGRAM OF GENERAL EDUCATION IN THE SECONDARY SCHOOL. - Caldwell, Loren T. (Science Education, 1955)
The article investigates the determination of earth science principles desirable for inclusion in the science program of general education in the secondary school. It derives from an analysis of published materials in the earth sciences those principles which may be used in the science program of general education in the secondary school. It determines the relative importance of earth science principles which are desirable for inclusion in the science program of general education in the secondary school. The investigation consisted of three phases such as, the compilation of source materials in the earth sciences, an analysis of selected earth science sources for statements of tentative earth science principles, and the determination of the relative importance of earth science principles which are desirable for inclusion in the science program of general education in the secondary school.